What Makes Teachers Well? A Mixed Methods Study of Special Education Teacher Well-being - Fox, Harriet B.; Tuckwiller, Elizabeth D.; Kutscher, Elisabeth L.; Walter, Heather L. (Journal of Interdisciplinary Studies in Education, 2021)
Using a longitudinal convergent-mixed-methods approach, researchers explored how secondary special education teachers understand and experience well-being in their work as educators. Researchers were interested in how teachers’ reported levels of well-being, as well as interpretations of well-being, shifted over the course of the school year. Evidence from this study suggests that teachers’ subjective experiences matter, but the contexts in which they teach can shift their experiences, which may be connected to overall well-being. Simply reducing stressors and/or burnout will not necessarily result in improved well-being for teachers. School-wide efforts to improve relationships within the school building, providing space for teacher leadership, explicitly naming shared values, and recognizing the emotional calendar of the school year may facilitate teachers’ well-being.